2021
DOI: 10.1039/d1ma00080b
|View full text |Cite
|
Sign up to set email alerts
|

Capacity and phase stability of metal-substituted α-Ni(OH)2 nanosheets in aqueous Ni–Zn batteries

Abstract: Batteries that offer high specific energy and energy density coupled with improved safety and lower cost will affect applications ranging from electric vehicles, portable electronic devices, and grid-level energy storage....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Finally, by increasing the heating time from 30 min to 90 min at 220 °C, the sample retains the β-phase with a slight shift in all peak positions except for (001) and (111). These shifts are attributable to bigger or smaller interlayer spacings occurring from differences in the quantities and coordination of water [ 41 ]. Additionally, the peaks become broader and lower, which indicates that the crystallinity is weaker than N.A.220C.30m.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, by increasing the heating time from 30 min to 90 min at 220 °C, the sample retains the β-phase with a slight shift in all peak positions except for (001) and (111). These shifts are attributable to bigger or smaller interlayer spacings occurring from differences in the quantities and coordination of water [ 41 ]. Additionally, the peaks become broader and lower, which indicates that the crystallinity is weaker than N.A.220C.30m.…”
Section: Resultsmentioning
confidence: 99%
“…[81,90] Additionally, Diaz-Morales et al [91] showed that Zn-doped Ni-(OH) 2 cathode requires an increased overpotential for oxygen evolution reaction; thus, as an additive, it is less suited for oxygen generation catalysis, albeit this result might be beneficial for utilizing this material for cathode formulation and design. [92,93] Table 2 provides a summary of the inorganic additives being utilized with the aim to improve the performance of the NiOOH cathode.…”
Section: Additive's Rolementioning
confidence: 99%
“…The α-Ni(OH) 2 layer forming on the electrode surface exhibits an insulating behavior. The β-Ni(OH) 2 , on the other hand, is thermodynamically stable in alkaline solutions, but offers a much lower theoretical capacity of 289 mAh g −1 , with practical capacities ranging from 237 to 263 mAh g −1 [61]. This is because the transformation to β-NiOOH only involves a single electron transfer.…”
Section: Positive Electrodementioning
confidence: 99%